1997
DOI: 10.1042/bj3270369
|View full text |Cite
|
Sign up to set email alerts
|

Acute regulation of glucose transport in a monocyte–macrophage cell line: Glut-3 affinity for glucose is enhanced during the respiratory burst

Abstract: Activation of the respiratory burst imposes acute metabolic demands on phagocytic cells. These are met by mobilizing internal energy stores and by increasing the utilization of exogenous energy, including glucose in the circulation. To determine whether the increased glucose uptake that is known to be associated with the respiratory burst involves the regulation of glucose transporter molecules, the intrinsic transport properties of glucose transporters on the macrophage cell line RAW 264.7 were determined aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 46 publications
6
52
0
3
Order By: Relevance
“…The consumption of glucose by inflammatory macrophages is mediated by glucose surface receptors and has been well characterized in numerous studies. 25,26 Those studies have shown that cellular glucose uptake agrees well with the MichaelisMenten formalism for enzymatic activity. As a result, consumption can be modeled using Michaelis-Menten kinetics with values specific to glucose uptake by macrophages.…”
Section: Modeling Early Stage Sensor Responsementioning
confidence: 76%
“…The consumption of glucose by inflammatory macrophages is mediated by glucose surface receptors and has been well characterized in numerous studies. 25,26 Those studies have shown that cellular glucose uptake agrees well with the MichaelisMenten formalism for enzymatic activity. As a result, consumption can be modeled using Michaelis-Menten kinetics with values specific to glucose uptake by macrophages.…”
Section: Modeling Early Stage Sensor Responsementioning
confidence: 76%
“…We found that GLUT-1 and GLUT-3, which are major isoforms of a glucose transporter in macrophages (12,13), were significantly upregulated in M1 macrophages, compared with M2 macrophages (Fig. 3) (P , 0.01 and , 0.01, respectively).…”
Section: Expression Of Glucose Metabolism-related Genes In Macrophagesmentioning
confidence: 81%
“…GLUT-1 is the major isoform found in most cells, whereas GLUT-3 leads to a substantial increase in energy needs associated with cell activation by its high affinity for glucose 30 and is a major GLUT subtype for macrophages. [31][32][33] Both GLUT-1 and GLUT-3 immunoreactivity were shown to be distributed in macrophages of the aneurysmal wall, indicating that glycolysis is the preferred energy production of these cells than the other cell types constituted of aorta. Importantly, the magnitude of GLUT-3 expression was associated with MMP-9 activity, mainly produced from macrophages in aneurysmal tissues, 34 and this was comparable in a monocytic cell line, showing the substantial increase in syntheses in GLUT-3 and MMP-9 upon the differentiation to macrophages.…”
Section: Discussionmentioning
confidence: 99%